Identification of ESM-1 as a new endothelial biomarker in the pathogenesis of rheumatoid arthritis. Issue 3 (3rd May 2016) - Ciftci, Gönül Gürol; Ciftci, Ihsan Hakkı; Karakece, Engin; Harman, Halil; Kamanlı, Ayhan; Tekeoglu, Ibrahim
ABSTRACT: The aim of this study was to investigate the use of ESM-1 (endothelial cell-specific molecule-1) as a new biomarker for the pathogenesis of rheumatoid arthritis (RA). The study cohort was divided into four groups according to the DAS28 disease activity score: 16 patients were classified as being in remission (DAS28 < 2.6), 16 patients exhibited low disease activity (DAS28: 2.6–3.2), 20 patients exhibited moderate disease activity (DAS28: 3.2–5.1) and 16 patients exhibited high disease activity (DAS28 > 5.1); 20 healthy subjects were included as a control group. Serum samples were gathered from the patients with documented seropositivity for rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibodies in order to assess RF IgM and ESM-1. ESM-1 levels were significantly higher in patients with RA than in healthy subjects ( p = 0.035). The data presented here strongly indicate ESM-1 as an attractive target for the treatment of inflammation-related diseases, such as RA.